THE ANALYSIS OF THE EFFECTS OF PRICE, PROMOTION, AND PRODUCT RATINGS ON PURCHASING DECISIONS IN ONLINE MARKETPLACES - Narita Maulidya Putri; Eloh Bahiroh (PT Larva Wijaya Penerbit, 2024)
The end of this reaserch is to dissect the factors of copping opinions by consumers, similar as the effect of price, creation, and product standing which are taken into consideration through the online business. this exploration also discusses consumer geste towards copping opinions.